Analyzing the Savings-Investment Trend in a Panel of G-7 Countries - Mansoor, Abdul; Sultana, Baserat; Saeed, Romana (Asian Journal of Economics and Empirical Research, 2018)
This study examined the relationship between savings and investment in the G-7 countries for the period of 1970 to 2015. The stationary analysis of the data has been done by adopting the panel Levin, Lin & Chu, Breitung, Pesaran & Shin, ADF-Fisher & PP-Fisher criteria while the long run relationship has been tested by employing the Pedroni residual test of co-integration. The results neglected the existence of a long run correlation between saving and investment in G-7 countries. Further, joint causality between the savings and investment has also been tested using the fixed effect VAR model. Wald test explains that the two consecutive lags i.e. S (-1) and S (-2) of savings is jointly causing savings in the current year in the G7 countries. While the same two lags of investment i.e. I (-1) and I (-2) does not jointly granger cause savings in the G7 economies. The results are in line with Feldstein and Horioka (1980) that there is a stable and significant association between the increasing rates of savings and investment in the short run while this relationship weaken in the long run.